2022
DOI: 10.4048/jbc.2022.25.e17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Breast and Axillary Pathologic Complete Response According to Clinical Nodal Stage: A Nationwide Study From Korean Breast Cancer Society

Abstract: Purpose We evaluated the relationship between breast pathologic complete response (BpCR) and axillary pathologic complete response (ApCR) after neoadjuvant chemotherapy (NACT) according to nodal burden at presentation. As the indications for NACT have expanded, clinicians have started clinical trials for the omission of surgery from the treatment plan in patients with excellent responses to NACT. However, the appropriate indications for axillary surgery omission after excellent NACT response remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Differences in the way subjects clinically defined cN0 and the biological subtypes included in subjects, the proportions achieving breast pCR varied widely for the overall ypN+ rates observed in each cN0 breast cancer patient undergoing NAC [ 25 , 26 , 27 , 34 , 35 , 36 , 37 , 38 ]. Murphy et al reported a ypN+ rate of 22% in patients registered in the National Cancer Database, without knowing whether axillary ultrasound was routinely performed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences in the way subjects clinically defined cN0 and the biological subtypes included in subjects, the proportions achieving breast pCR varied widely for the overall ypN+ rates observed in each cN0 breast cancer patient undergoing NAC [ 25 , 26 , 27 , 34 , 35 , 36 , 37 , 38 ]. Murphy et al reported a ypN+ rate of 22% in patients registered in the National Cancer Database, without knowing whether axillary ultrasound was routinely performed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lower ypN+ rate of only 3.4% was observed in a prospective cohort study by Tadros et al in the cN0 subgroup that included only triple-negative and HER2-positive breast cancers [ 26 ]. In a study conducted by Ryu et al using the Korean Breast Cancer Society Registry database, all patients with cT1-3N0 were found to have a breast pCR rate of 19.7% and a ypN+ rate of 16.7% regardless of the biological subtype [ 38 ]. In our study, the low ypN+ rate of 7.7% could be explained by routine axillary ultrasound combined with ultrasound-guided fine needle aspiration or core needle biopsy to confirm cN0 status; nearly 60% of patients had triple-negative or HER2-positive breast cancer and all populations had a high probability of achieving breast pCR of 40.5% regardless of biological subtype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations